Impacts of Globalization on Human Rights - Munawar Sabir (Journal of Political Studies, 2014)
Globalization is one of the most articulated, and experienced phenomenon which has resulted from the increasing interdependence and interpenetration of nations, communications, and flow of ideas across the borders, is one of the conspicuous dimensions of the current world. International standards and actors for the protection of human rights are ever more advanced and practically active than ever in human history. But violation and encroachment on basic human dignity continues, and the rise of international actors that generated the development of human rights globally may also be the cause of new ways and means of negation of human rights .In globalized world human rights are no more a question of national actors but more dependent on the international and global actors and institutions as multinational companies, media and others. Human rights have become a multidimensional term as it encompasses social but political and economic aspects as well.